Propagation of wind turbine noise: measurements and model evaluation. Issue 3 (1st May 2022) - Nyborg, C M; Fischer, A; Thysell, E; Feng, J; Søndergaard, L S; Sørensen, T; Hansen, T R; Hansen, K S; Bertagnolio, F
Abstract: Sound propagation from wind turbines through the atmosphere has previously been analytically examined through numerous studies, but the amount of comparisons to measurements is limited. This paper applies three different sound propagation models; The ISO 9613-2 model, the Nord2000 ray tracing model and the WindSTAR-Pro model, to evaluate the noise at receivers in the near- and far-field of a wind turbine. The evaluation is performed by accounting for different meteorological and terrain parameters. For validation purposes, the study further uses two different data sets from measurement campaigns; Loudspeaker noise and wind turbine noise measurements. The validation evidently shows that especially the WindSTAR-Pro model and the Nord2000 model provide good agreement to the measurements for some of the validation cases, while other results are heavily influenced by the turbine wake, signal to noise ratio in the measurements or directivity of the noise source.